2016
DOI: 10.1016/j.cell.2016.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Immunization Elicits Broadly Neutralizing Anti-HIV-1 Antibodies in Ig Knockin Mice

Abstract: Summary A vaccine that elicits broadly neutralizing antibodies (bNAbs) against HIV-1 is likely to be protective, but this has not been achieved. To explore immunization regimens that might elicit bNAbs, we produced and immunized mice expressing the predicted germline of PGT121, a bNAb specific for the V3-loop and surrounding glycans on the HIV-1 spike. Priming with an epitope modifiied immunogen designed to activate germline antibody-expressing B cells, followed by ELISA-guided boosting with a sequence of dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
346
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(360 citation statements)
references
References 82 publications
(195 reference statements)
10
346
0
Order By: Relevance
“…Alternatively, the most efficient strategy may be sequential immunization followed by a mixture of variant Ags, as in ref. 35. Study of these situations to determine optimal conditions as we report here, both computationally and experimentally, is an important direction of future research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the most efficient strategy may be sequential immunization followed by a mixture of variant Ags, as in ref. 35. Study of these situations to determine optimal conditions as we report here, both computationally and experimentally, is an important direction of future research.…”
Section: Discussionmentioning
confidence: 99%
“…These in silico predictions were tested in model experiments in mice. A recent report (35) provides further experimental support for this strategy. Luo and Perelson (36) subsequently reported that, during the coevolution of viral strains and Ab responses after infection, Ab breadth increased with the number of variant Ags and the mutational distances separating them.…”
Section: Significancementioning
confidence: 96%
See 1 more Smart Citation
“…This type of narrow-specificity response may serve as a necessary starting point for strategies intended to create neutralization breadth (7,(33)(34)(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
“…Given previous observations for malaria AMA1 and influenza HA, it would be interesting to test an HIV vaccine comprised of several Env proteins from different clades, preferably the native (SOSIP conformation [75]) expressed on a polyvalent VLP. Indeed, mixtures of five native-like SOSIPs differing in the variable loops have recently been used as a final boost for the induction of PGT121 like bnAb [76]. However, the full potential of this strategy, especially the expression of multiple variants on a single particle, has not yet been explored.…”
Section: Edip For Other Variable Vaccine Antigensmentioning
confidence: 99%